Association Between Dietary Iron Intake and Serum Ferritin and Severe Headache or Migraine - Meng, Shu-Han (Front Nutr, 2021)
Background: Dietary iron intake and serum ferritin in relation to severe headache or migraine remain largely unknown. Therefore, we investigated the associations between dietary iron intake and serum ferritin with severe headache or migraine among American adults. Methods: This cross-sectional study included 7,880 adults (≥20 years) from the National Health and Nutrition Examination Surveys (NHANES) of America from 1999 to 2004. We performed multivariable logistic regression and restricted cubic spline (RCS) regression to assess the association of dietary iron and serum ferritin with severe headache or migraine. Results: Most women aged 20–50 years consumed less dietary iron than their recommended dietary allowances. Dietary iron intake was inversely associated with severe headache or migraine in women aged 20–50 years. For women over 50 years, serum ferritin was negatively associated with severe headache or migraine. For men, there was no significant relationship between dietary iron and serum ferritin, and severe headache or migraine. Conclusions: Dietary iron intake has different effects on migraine in women of different ages, and this different effect may be due to age-related menstrual changes. Women aged 20–50 years should have a higher awareness of RDA and increase their dietary iron intake if needed, which may play an important role in preventing severe headache or migraine. Higher serum ferritin levels in women aged 50 and above may have a protective effect against migraine.